Embarking on a journey: unraveling cultural tapestry in the realm of in-service English language instructors within a Malaysian higher education haven - Sultana, Tanzima; Ali Abdalla, Mwana; Abdullah, Mohamad Ridhuan (Persatuan Sains Sosial dan Kemanusiaan Muallim, 2024)
This study explores how English language instructors (ELIs) at a Malaysian international university comprehend cultural diversity, apply culturally responsive teaching in their classrooms, and align their practices with Banks's four levels of ethnic content integration. Through qualitative case analysis, we interviewed five seasoned ELIs, aiming to unravel the connection between their beliefs and teaching methods. Understanding teachers' perceptions is crucial for the successful implementation of multicultural education. Our inductive thematic analysis reveals that instructors at the selected university possess only a surface-level grasp of cultural diversity. Interestingly, their perception and incorporation of cultural diversity elements into ELIs don't align with Banks's model. Furthermore, teachers' beliefs are rooted in a color-evasive ideology, influencing their reflexivity and efforts to foster culturally responsive teaching. This study's findings offer valuable insights for refining teacher training programs, ensuring a more effective implementation of culturally responsive instruction in educational institutions characterized by diverse student populations.